Importance of daptomycin dosage on the clinical outcome in liver transplant recipients with vancomycin-resistant enterococci infection. (20th September 2022) - Lee, Ing-Kit; Sng, Yi-Ping; Li, Wei-Feng; Chen, Chao-Long; Wang, Chih-Chi; Lin, Chih-Che; Chen, I-Ling
Abstract: We retrospectively studied 16 (3 colonization and 13 infections) early post-liver transplant (≤60-day after transplantation) patients with vancomycin-resistant enterococci (VRE) colonization/infection from 2016 to 2019. All VRE isolates were Enterococcus faecium . Of 13 patients with VRE infection, 12 (92.3%) underwent living-donor liver transplantation and 1 underwent deceased donor liver transplantation. Among these 13 patients, the median time from transplant to emergence of VRE infection was 12 days. The median interval from VRE infection to death was 27 days. Of these 13 patients, eleven patients (8 survived; 3 died) received daptomycin therapy for VRE. Among them, 4 (36.3%) received daptomycin doses <8 mg/kg. Non-survivors ( n = 3) received significantly lower daptomycin dose than survivors ( n = 8; p = .040). Daptomycin doses <8mg/kg were more frequently associated with non-survivors ( n = 3) than with survivors ( n = 8; p = .024). In summary, the suboptimal dosage of daptomycin may have contributed to a higher rate of in-hospital mortality. Doses ≥8 mg/kg may be needed to adequately treat VRE infection in liver transplant recipients.